Melatonin as a Smart Protector of Pregnancy in Dairy Cows - Essa Dirandeh; Zarbakht Ansari-Pirsaraei; William Thatcher (MDPI AG, 2022)
The experimental objective was to examine the role of melatonin and its pathways in the maintenance of pregnancy in lactating dairy cows. Blood samples were collected at days 0, 16 and 32 after timed AI from cows (n = 200) in order to consider plasma melatonin concentrations and to conduct AOPP (advanced oxidation products of proteins) and TBARS (thiobarbituric acid reactive substances) tests. Luminal endometrial cells were collected at day 16 using a Cytobrush in all cows to determine mRNA expressions of melatonin receptor 1 (MT1), mouse double minute 2 (MDM2), MDM2 binding protein (MTBP), BCL2-associated X, apoptosis Regulator (BAX), p53 upregulated modulator of apoptosis (PUMA, gene symbol BBC3), mucin 1 (MUC1) and leukemia inhibitory factor (LIF). Plasma concentrations of melatonin were significantly greater in pregnant cows diagnosed pregnant at day 16 who sustained pregnancy to day 32 compared to nonpregnant cows at day 16, or pregnant at day 16 and who lost embryos by days 32. Concentrations of AOPP and TBARS were greater in nonpregnant cows at day 16 or pregnant at day 16 and who lost embryos by days 32 compared to those diagnosed pregnant at day 16 and who sustained pregnancy to day 32. In pregnant cows, endometrial mRNA expressions of MDM2, MTBP, MTR1 and LIF were higher compared to pregnant-embryo-loss cows (p < 0.05). In contrast, mRNA expressions of BBC3 and MUC1 were greater at day 16 in pregnant-embryo-loss cows compared to pregnant cows (p < 0.05). In conclusion, melatonin status is a modulator of embryo well-being and maintenance of pregnancy in lactating dairy cows.